An any-cell(s)-to-cell(s) equalization method with a single magnetic component for Lithium-ion battery pack. (January 2021) - Chen, Yang; Liu, Xiaofang; Shen, Teng; Cheng, Lefeng; Wang, Xiaogang; Yang, Ru; Yang, Shiyan
Highlights: A single magnetic bi-directional active equalization method is developed The proposed method can achieve equalization with multiple balancing paths The impact factors of the average balancing current is first evaluated Abstract: This paper develops a bi-directional active equalization method using an inductor with multiple balancing paths. The new method allows the energy to transfer directly from any cell(s) to any cell(s) which can increase the equalization speed, reduce the energy conversion times and efficiently prevent the batteries from overcharging or undercharging. We adopt the bi-directional switches of low conduction loss for high equalization efficiency. To further improve the battery equalization system performance, the impact factors of the average balancing current which is the main measurement index of the balancing speed are first specifically discussed and the efficiency is also evaluated. The experiments with a four-20Ah Lithium-ion battery string are conducted and the results demonstrate that the developed approach has achieved a good overall performance of equalization.